(untitled) (Italian Journal of Public Health, 2012)
Background: increased life expectancy and an aging population have made home care for the elderly a major responsibility for families. Caring for a chronically ill or physically disabled person has been referred to as physically or emotionally stressful, placing the caregiver at a heightened risk of burden. This study aimed to identify factors related to caregiving burden among caregivers who care for their disabled older family members. Methods: a cross sectional descriptive study was conducted from October 2008 to January 2009 in two randomly selected villages of Shebin El-Kom Menoufiya, Egypt. In an interview setting, questionnaires were used to collect the required data from 288 primary caregivers. Independent variables included the demographic characteristics of caregivers and care recipients, the severity of care recipients’ functional abilities, financial adequacy and caregivers’ degree of social support. Hierarchical regression was used to predict the levels of caregiver burden. The objective of the study was adequately explained to participants and their consent was obtained with assured confidentiality. Results: caregivers who had little informal social support, inadequate financial resources and more caregiving hours were more likely to experience intense caregiving burden. Burden was also positively associated to the functional disabilities of care recipients and the degree of caregiver burnout. The results of this study indicated that the female spouse was the most common caregiver within the sample, which indicates that cultural norms in Egypt still affect caregiving burden. Conclusions: identifying predictors of caregiver burden promotes a more comprehensive understanding of burden experiences when caring for older adults, and this may help prevent their deterioration to burn out syndrome